[18F](2S,4R)-4-Fluoroglutamine as a New Positron Emission Tomography Tracer in Myeloma - Valtorta, Silvia; Toscani, Denise; Chiu, Martina; Sartori, Andrea; Coliva, Angela; Brevi, Arianna; Taurino, Giuseppe; Grioni, Matteo; Ruffini, Livia; Vacondio, Federica; Zanardi, Franca; Bellone, Matteo; et al. (Frontiers in Oncology, 2021)
The high glycolytic activity of multiple myeloma (MM) cells is the rationale for use of Positron Emission Tomography (PET) with 18F-fluorodeoxyglucose ([18F]FDG) to detect both bone marrow (BM) and extramedullary disease. However, new tracers are actively searched because [18F]FDG-PET has some limitations and there is a portion of MM patients who are negative. Glutamine (Gln) addiction has been recently described as a typical metabolic feature of MM cells. Yet, the possible exploitation of Gln as a PET tracer in MM has never been assessed so far and is investigated in this study in preclinical models. Firstly, we have synthesized enantiopure (2S,4R)-4-fluoroglutamine (4-FGln) and validated it as a Gln transport analogue in human MM cell lines, comparing its uptake with that of 3H-labelled Gln. We then radiosynthesized [18F]4-FGln, tested its uptake in two different in vivo murine MM models and checked the effect of Bortezomib, a proteasome inhibitor currently used in the treatment of MM. Both [18F]4-FGln and [18F]FDG clearly identified the spleen as site of MM cell colonization in C57BL/6 mice, challenged with syngeneic Vk12598 cells and assessed by PET. NOD.SCID mice, subcutaneously injected with human MM JJN3 cells, showed high values of both [18F]4-FGln and [18F]FDG uptake. Bortezomib significantly reduced the uptake of both radiopharmaceuticals in comparison with vehicle at post treatment PET. However, a reduction of glutaminolytic, but not of glycolytic, tumor volume was evident in mice showing the highest response to Bortezomib. Our data indicate that [18F](2S,4R)-4-FGln is a new PET tracer in pre-clinical MM models, yielding a rationale to design studies in MM patients